1977
DOI: 10.1113/jphysiol.1977.sp012033
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiac output and total peripheral resistance during the carotid sinus baroreceptor reflex in the pregnant rabbit.

Abstract: SUMMARY1. The reflex cardiovascular effects of changes in pressure within the isolated carotid sinus have been examined in sixteen anaesthetized pregnant rabbits.2. Comparison of the mean results at sinus pressures of 40 and 200 mmHg showed that heart rate fell by 32-1 beats min-' and arterial pressure was reduced by 48-2 mmHg. Cardiac output, measured by thermal dilution, fell by 25-7 ml. min-'.kg-1 and total peripheral resistance was reduced by 0-292 mmHg.ml.-' min.kg.3. The corresponding changes previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
4
14
0
Order By: Relevance
“…The present study examines the possibility that the lower total peripheral resistance at all levels of carotid sinus pressure noted by Humphreys & Joels (1977) derives in part from changes induced by pregnancy in vascular beds other than those directly concerned with reproduction. The circulation to the hind-limb musculature is an example of such a vascular bed.…”
Section: P W Humphreys and N Joelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study examines the possibility that the lower total peripheral resistance at all levels of carotid sinus pressure noted by Humphreys & Joels (1977) derives in part from changes induced by pregnancy in vascular beds other than those directly concerned with reproduction. The circulation to the hind-limb musculature is an example of such a vascular bed.…”
Section: P W Humphreys and N Joelsmentioning
confidence: 99%
“…A comparison of the carotid sinus baroreceptor reflex in pregnant and non-pregnant rabbits has shown that, at all levels of carotid sinus pressure, total peripheral resistance is lower in pregnant rabbits (Humphreys & Joels, 1977); at sinus pressures between 75 and 110 mmHg, which encompassed the range of arterial pressures in the majority of the rabbits, this reduction was in the region of 20-25 %, and was accompanied by a similar reduction in blood pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change was first noted by Humphreys and Joels (97,98) in an extensive series of studies in anesthetized pregnant rabbits, in which reductions in carotid sinus pressure failed to elicit normal increases in arterial pressure and peripheral vascular resistance. Since then, arterial baroreflex impairment has been documented in several species studied in the conscious state, including dogs (23), rats (24,124), rabbits (21,97,162), goats (152), sheep (104,123), and humans (16,79,122,164,175,193).…”
mentioning
confidence: 99%
“…Cardiac output was measured at intervals by thermal dilution as described previously (Humphreys & Joels, 1977 a). 0-6 ml 0-9 % NaCl at room temperature was injected from a calibrated syringe into the right atrium via a catheter passed through the right external jugular vein until its tip lay just proximal to the entry of the superior vena cava into the right atrium.…”
Section: Methodsmentioning
confidence: 99%